2020
DOI: 10.1101/2020.09.30.321075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune Lag Is a Major Cost of Prokaryotic Adaptive Immunity During Viral Outbreaks

Abstract: CRISPR adaptive immune systems enable bacteria and archaea to efficiently respond to viral pathogens by creating a genomic record of previous encounters. These systems are broadly distributed across prokaryotic taxa, yet are surprisingly absent in a majority of organisms, suggesting that the benefits of adaptive immunity frequently do not outweigh the costs. Here, combining experiments and models, we show that a delayed immune response which allows viruses to transiently redirect cellular resources to reproduc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…It is possible that viral abundance rarely reaches levels in nature that are sufficient to preclude an effective CRISPR-Cas response, even if such densities are readily achievable in laboratory experiments. 9,10,24 Future work may reveal the ecological differences between CRISPR-Cas types, as different types are likely to coevolve with viruses in fundamentally different ways. 25 Genomic evidence demonstrates that CRISPR-Cas systems are frequently acquired and lost, 26,27 and empirical studies show that they can be mobilized through HGT.…”
Section: Reportmentioning
confidence: 99%
“…It is possible that viral abundance rarely reaches levels in nature that are sufficient to preclude an effective CRISPR-Cas response, even if such densities are readily achievable in laboratory experiments. 9,10,24 Future work may reveal the ecological differences between CRISPR-Cas types, as different types are likely to coevolve with viruses in fundamentally different ways. 25 Genomic evidence demonstrates that CRISPR-Cas systems are frequently acquired and lost, 26,27 and empirical studies show that they can be mobilized through HGT.…”
Section: Reportmentioning
confidence: 99%
“…However, the CRISPR systems distribute unevenly across the prokaryotic phylogeny and environments [41] despite these high rates of HGT. This apparent paradox has been explained by direct fitness costs of the CRISPR system or reduced benefit due to competition from other immune systems [14,18,[42][43][44]. For instance, acquiring self-targeting spacers is deleterious to the host [45][46][47]; CRISPR may prevent HGT so that the acquisition of advantageous mobile genetic elements (MGEs) is limited [48][49][50][51]; CRISPR shows negative epistasis with host genes in some cases [41,52].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CRISPR-Cas-mediated immunity in bacteria comes with inducible costs upon phage infection [9, 10]. These costs arise directly from the expression of the CRISPR array and cas genes upon infection [11, 12] as well as indirectly from the time lag between the start of phage gene expression and the clearance by the CRISPR system [13, 14]. Even short-term expression of phage genes can be toxic and leads to reduced fitness of the host [13].…”
Section: Introductionmentioning
confidence: 99%